If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k + -2k + -3 = -12 Reorder the terms: -3 + 3k + -2k = -12 Combine like terms: 3k + -2k = 1k -3 + 1k = -12 Solving -3 + 1k = -12 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1k = -12 + 3 Combine like terms: -3 + 3 = 0 0 + 1k = -12 + 3 1k = -12 + 3 Combine like terms: -12 + 3 = -9 1k = -9 Divide each side by '1'. k = -9 Simplifying k = -9
| r^2-6r-71=0 | | k|3=8 | | 36=2x^2 | | 4x-2-2x=9x-x | | 3n+5n=40 | | -6+2*-4-3*6= | | 2+(1.5p)=2.5+(1p) | | 10x-8(0)=16 | | 11-4x+15=14 | | 5(n+9)= | | a^2+18a+85=0 | | -3/7=-4u | | -0.7x+0.2x+4=1 | | 2x+9=3x-17 | | 6x-2(1)=16 | | 9v-2v=19 | | f=5+-9(-2)-1 | | 6(2)-2y=16 | | 4x-12+3x+6=180 | | 6(0)-2y=16 | | -z+6z=7z-3+7z | | y-5=.06(x-3) | | 1=0.2x-0.8x-47 | | 6x-2(0)=16 | | 12m+6=9m-54 | | y=1-4(1)+4 | | 9-14x-6-7x=6 | | y=25-4(5)+4 | | -7.625=1.8333333+d | | 7y-2=47 | | 5(1-7n)= | | y-(0.1304347826)=-0.08695652173 |